Development of an SPME‐GC‐MS method for the specific quantification of dimethylamine and trimethylamine: use of a new ratio for the freshness monitoring of cod fillets. (25th January 2016) - Dehaut, Alexandre; Duthen, Simon; Grard, Thierry; Krzewinski, Frédéric; N'Guessan, Assi; Brisabois, Anne; Duflos, Guillaume
Abstract: BACKGROUND: Fish is a highly perishable food, so it is important to be able to estimate its freshness to ensure optimum quality for consumers. The present study describes the development of an SPME‐GC‐MS technique capable of quantifying both trimethylamine (TMA) and dimethylamine (DMA), components of what has been defined as partial volatile basic nitrogen (PVB‐N). This method was used, together with other reference methods, to monitor the storage of cod fillets ( Gadus morhua ) conserved under melting ice. RESULTS: Careful optimisation enabled definition of the best parameters for extracting and separating targeted amines and an internal standard. The study of cod spoilage by sensory analysis and TVB‐N assay led to the conclusion that the shelf‐life of cod fillet was between 6 and 7 days. Throughout the study, TMA and DMA were specifically quantified by SPME‐GC‐MS; the first was found to be highly correlated with the values returned by steam distillation assays. Neither TMA‐N nor DMA‐N were able to successfully characterise the decrease in early freshness, unlike dimethylamine/trimethylamine ratio (DTR), whose evolution is closely related to the results of sensory analysis until the stage where fillets need to be rejected. CONCLUSION: DTR was proposed as a reliable indicator for the early decrease of freshness until fish rejection. © 2015 Society of Chemical Industry